Multiple biomarkers and arrhythmia outcome following catheter ablation of atrial fibrillation: The Guangzhou Atrial Fibrillation Project. Issue 6 (31st August 2018) - Deng, Hai; Shantsila, Alena; Guo, Pi; Zhan, Xianzhang; Fang, Xianhong; Liao, Hongtao; Liu, Yang; Wei, Wei; Fu, Lu; Wu, Shulin; Xue, Yumei; Lip, Gregory Y.H.
Abstract: Background: Biomarkers have been related to the arrhythmia recurrence following catheter ablation (CA) of atrial fibrillation (AF). We hypothesized that concurrent measurement of several biomarkers would additively improve their predictive value. Methods: One thousand four hundred and ten consecutive AF patients (68% male; 57.2 ± 11.6 years) undergoing CA were enrolled. Baseline characteristics, serum B type brain natriuretic peptide (BNP) and high sensitivity C reactive protein (hsCRP), estimated glomerular filtration rate (eGFR), ablation parameters, arrhythmia data at discharge, 1, 3, 6, and then every 6 months post CA were collected. Follow‐up ended when arrhythmia recurred or until 31st December 2016. Results: Three hundred and sixty‐five (25.9%) patients had arrhythmia recurrence post‐CA during a mean follow‐up of 20.7 ± 8.8 months. BNP, hsCRP, and eGFR levels and their cut‐off values of 237.45 pg/mL, 1.6 mg/dL, and 82.5 mL/min/1.73 m 2 were good predictors for AF recurrence (all P < 0.01). On multivariate analysis, increasing BNP and hsCRP, decreasing eGFR, gender, and early recurrence (ER) were independent predictors of AF recurrence (all P < 0.01). Compared to BNP alone, BNP plus eGFR or both eGFR and CRP showed incrementally better predictive values (ROC comparisons, all P < 0.01). Similar findings were evident in the subgroups of patients with paroxysmal or nonparoxysmal AF. Conclusion: Measurement of BNP, CRP, and eGFR were incrementally additive to clinical risk factors in a cumulative manner to improve prediction of arrhythmia recurrence post‐CA of AF. The implications of poor arrhythmia outcome in AF patients with multiple abnormal biomarkers pre‐CA procedure may help with patient selection and inform the likelihood of success or the need of more complicated CA procedure(s).